2022
DOI: 10.1017/s0007114522004019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bioelectrical impedance analysis in measuring body fat in 6-to-12-year-old boys compared with air displacement plethysmography

Abstract: Air displacement plethysmography (ADP) has been considered the ‘standard’ method to determine body fat in children due to superior validity and reliability compared to bioelectrical impedance analysis (BIA). However, ADP and BIA are used interchangeably despite few studies comparing measures of percentage body fat by ADP (%FMADP) with BIA (%FMBIA) in children with and without obesity. The objective of this study was to measure concurrent validity and reliability of %FMADP and %FMBIA in 6-to-12-year-old boys wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…A previous study showed that good agreement and interchangeability of these two methods were not found in 7- to 13-year-old Belgian boys ( 29 ). Mahaffey et al ( 30 ) reported that BIA and ADP cannot be used interchangeably in boys aged 6 to 12 years in the UK. Compared with the percent BF by ADP, the percent BF by BIA was significantly underestimated in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that good agreement and interchangeability of these two methods were not found in 7- to 13-year-old Belgian boys ( 29 ). Mahaffey et al ( 30 ) reported that BIA and ADP cannot be used interchangeably in boys aged 6 to 12 years in the UK. Compared with the percent BF by ADP, the percent BF by BIA was significantly underestimated in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these factors, in addition to the low number that experienced clinically significant weight loss, likely fail to reflect the true nature of muscle loss and body composition changes in the heterogenous population included in the pilot. In fact, the use of air-displacement plethysmography has grown increasingly popular to assess body composition given no radiation exposure, high reliability, and ease of analysis and would be an ideal tool to obtain more accurate measurements of changes in children undergoing cancer treatment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%